Anticancer potential of Spirastrella pachyspira (marine sponge) against SK-BR-3 human breast cancer cell line and in silico analysis of its bioactive molecule sphingosine - Morais, Shabna Roupal; K, Chitra; Jeyabalan, Srikanth; Wong, Ling Shing; Sekar, Mahendran; Chidambaram, Kumarappan; Gan, Siew Hua; Begum, M. Yasmin; Izzati Mat Rani, Nur Najihah; Subramaniyan, Vetriselvan; Fuloria, Shivkanya; Fuloria, Neeraj Kumar; et al. (Frontiers in Marine Science, 2022)
The rate of breast cancer is rapidly increasing and discovering medications with therapeutic effects play a significant role in women's health. Drugs derived from marine sponges have recently received FDA approval for the treatment of malignant tumours, including metastatic breast cancer. Spirastrella pachyspira (marine sponge) is mainly obtained from the western coastal region of India, and its anticancer potential has not been explored. Hence, the present study aimed to evaluate the anticancer potential of Spirastrella pachyspira extracts and its bioactive molecule sphingosine. The extracts were prepared using hexane, chloroform, ethyl acetate, and ethanol. The cytotoxic potential of the extracts were determined by an in-vitro MTT assay using SK-BR-3 cancer cell line. Subsequently, acute toxicity investigation was conducted in Swiss albino mice. Then, the anticancer effects of the extract was investigated in a xenograft model of SK-BR-3 caused breast cancer. DAPI staining was used to assess the extract's ability to induce apoptosis. In addition, in-silico study was conducted on sphingosine with extracellular site of HER2. The ethyl acetate extract of Spirastrella pachyspira (IC50: 0.04 µg/ml) showed comparable anticancer effects with standard doxorubicin (IC50: 0.054 µg/ml). The LD50 of the extracts in acute toxicity testing was fund to be 2000 mg/kg b.wt. The survival index of mice in ethanol extract was 83.33%, whereas that of standard doxirubicin was 100%, indicating that ethyl acetate extract Spirastrella pachyspira has good antiproliferative/cytotoxic properties. The results were well comparable with standard doxorubicin. Further, the docking studies of sphingosine against HER2 demonstrated that the bioactive molecule engage with the extracellular region of HER2 and block the protein as also shown by standard trastuzumab. The findings of this research suggest that Spirastrella pachyspira and sphingosine may be potential candidate for the treatments of breast cancer, particularly for HER2 positive cells. Overall, the present results demonstrate that sphingosine looks like a promising molecule for the development of new drugs for the treatment of cancer. However, in order to carefully define the sphingosine risk-benefit ratio, future research should focus on evaluating in-vivo and clinical anticancer studies. This will involve balancing both their broad-spectrum effectiveness and their toxicity.